Investigating the Photocatalytic Behavior of Manganese-Zinc Ferrite and the Effect of Its Concentration on the Degradation of Methylene Blue in the Presence of Visible Light - S. Shahedi; S. Hasani; Z. Daneshfar; A.R. Mashreghi; Z. Zoghaghi (Journal of Advanced Materials in Engineering)
Methylene blue is widely used in various industries, such as textile. Notably, wastewater generated from these industries represents a significant source of water pollution. To solve this problem, the use of photocatalysts for the degradation of methylene blue in wastewater has attracted the attention of many researchers. In this study, manganese-zinc ferrite nanoparticles doped with dysprosium with the chemical composition of Mn0.8Zn0.2Fe1.95Dy0.05O4 were utilized as photocatalyst for the degradation of methylene blue dye. Initially, the nanoparticles were synthesized using a self-combustion sol-gel method, and their phase composition and microstructural characteristics were evaluated through X-ray diffraction and field emission scanning electron microscopy, respectively. The XRD patterns confirmed the formation of manganese-zinc ferrite nanoparticles with an average crystallite size of 28.38 nm within a spinel structure. Additionally, FE-SEM micrographs indicated an average particle size of approximately 99.28 nm for the nanoparticles. Subsequently, the influence of different values of the synthesized manganese-zinc ferrite nanoparticles (0.0, 0.1, 0.2, and 0.3 g/lit) on the degradation of methylene blue dye was investigated. The results demonstrated that the presence of these nanoparticles significantly affected the degradation rate of methylene blue. Ultimately, the findings indicated that the addition of 0.1 g/lit of these nanoparticles yielded the most effective results, achieving approximately 87.25% degradation in 12 h.